The Economic Impact of Public Rice Research in Thailand - Jaroensathapornkul, Jirawat (SOUTHEAST ASIAN JOURNAL OF ECONOMICS, 2007)
This study provides a measure of the current state of technicalknowledge determined in part by current and past public investment inrice research. With respect to the technical knowledge, rice productionfunction is estimated. The result reveals that the improvement of technicalknowledge enhances the land productivity and also leads to the changesin rice production structure. Since rice planted areas are expanded alongwith the employment of agricultural manual workers, the cost is no doubtincreased. The public rice research represents a crucial driving force forencouraging the growth of production. Further, the social welfare derivingfrom public investment in rice research is estimated by using Marshallianconcept. The result reveals that the cumulative economic surplus is quitehigh. As a consequence, the B/C ratio implies that those investments generatea benefit of 6.92, 6.25 and 5.68 Baht for every Baht spent by 5, 10 and15% discount rate, respectively.